The 2005 AISC Seismic Provisions for Structural Steel Buildings - Malley, James O. (Engineering Journal, 2007)
The American Institute of Steel Construction (AISC) standard, Seismic Provisions for Structural Steel Buildings, is the reference document for seismic design of steel structures throughout the United States. The 2003 International Building Code (IBC) incorporated these provisions by reference, and the 2002 National Fire Protection Association (NFPA) 5000 Building Code also followed this approach. Since their 1997 publication, the AISC Seismic Provisions have been updated on a regular basis in order to incorporate new developments from post-Northridge earthquake research on moment frames and other work in this area. The latest revision culminated with the publication of a completely new set of provisions in 2005 that is in the same unified format as the main AISC design specification. In addition, this edition makes reference to a new AISC standard for the pre-qualification of seismic moment connections that was also completed in 2005. Coordinated efforts between AISC and the Building Seismic Safety Council (BSSC) are intended to continue the process of keeping the seismic design provisions for structural steel buildings as current as possible. Efforts to coordinate with Canadian standards are also underway. This presentation will summarize the changes incorporated into the 2005 AISC Seismic Provisions and the use of the new moment connection pre-qualification standard. It will also speculate on future modifications and additions to the U.S. seismic design provisions for structural steel buildings.